A review and analysis of key biomarkers in Alzheimer’s disease - Zhang, Zhihao; Liu, Xiangtao; Zhang, Suixia; Song, Zhixin; Lu, Ke; Yang, Wenzhong (Frontiers in Neuroscience, 2024)
Alzheimer's disease (AD) is a progressive neurodegenerative disorder that affects over 50 million elderly individuals worldwide. Although the pathogenesis of AD is not fully understood, current knowledge allows researchers to identify potential biomarker genes and proteins that may serve as effective targets against AD. This article aims to presenting a comprehensive overview of recent advances in AD biomarker identification, with highlights on the use of various algorithms, the exploration of relevant biological processes, and the investigation of shared biomarkers with cooccurring diseases. Additionally, this article includes a statistical analysis of key genes reported in the research literature, and identifies the intersection with AD-related gene sets from databases such as AlzGen, GeneCard and DisGeNet. For these gene sets, besides enrichment analysis, proteinprotein interaction (PPI) networks are utilized to identify central genes among the overlapping genes.Enrichment analysis, protein interaction network analysis, and tissue-specific connectedness analysis based on GTEx database were performed on multiple groups of overlapping genes. Our work provides a foundation for better understanding the molecular mechanisms of AD and more accurate identification of key AD markers.